Enhanced treatment of m-dichlorobenzene waste gas in biotrickling filters: Performance, mass transfer and microbial community. Issue 2 (April 2023) - Wang, Jiajie; Yang, Bairen; Sun, Zhuqiu; Shang, Qingqing; Zhang, Junheng
Abstract: This study aimed to investigate the performance of biotrickling filters (BTFs) in the microbial degradation of m -dichlorobenzene ( m -DCB) to construct an enhanced treatment of removing m -dichlorobenzene ( m -DCB) at different concentrations of rhamnolipids (RLs) and lanthanum (La 3+ ) or neodymium (Nd 3+ ) ions. We found a significantly enhanced removal of m -DCB when 110 mg/L of RLs and 0.2 mg/L La 3+ or 0.4 mg/L Nd 3+ ions were added. The addition of RLs and La 3+ or Nd 3+ ions increased the m -DCB average removal efficiency (101–110 days) by 19.7% and 22.7%, respectively, when the inlet m -DCB concentration was 800 mg/m 3 and the empty bed residence time (EBRT) was 60 s. Further, the mechanisms that strengthened the mass transfer were the decrease of contact angle, surface tension, and Henry's constant after the addition of RLs and La 3+ or Nd 3+ ions in the nutrient solution; further, we noticed a significant increase in the dissolved oxygen levels. Improvements in the performance of BTFs were associated with enhanced microbial community and an increased abundance of functional genes. In conclusion, the addition of RLs and La 3+ or Nd 3+ ions can enhance the performance of BTFs in degrading m -DCB by improving mass transfer and microbial activity simultaneously. Graphical Abstract: ga1 Highlights: An enhanced treatment method of removing m -dichlorobenzene was constructed in biotrickling filters. The performance of biotrickling filters were enhanced by rhamnolipids and La 3+ or Nd 3+ ions. Rhamnolipids and La 3+ or Nd 3+ ions enhanced the gas-liquid mass transfer and microbial activity.